Perlindungan Konsumen Dalam Pandangan Sosiologi Dan Antropologi Hukum Ekonomi Syariah - Ikhsan, Muhammad Miftahul; Arifin, Tajul; Abdal, Abdal (Fakultas Syariah IAIN Kerinci, 2023)
sociology of Law is the study whose object is legal phenomena using the social sciences. The perspective used is seen from different sides. Because it refers to symptoms that occur in society. Anthropology is a scientific discipline whose focus of study lies on humans and culture in society. This type of research uses literature research that takes data through information by obtaining library materials, data techniques that have been obtained by reviewing and analyzing, both in the form of books, journals, research results. As well as by using descriptive analysis techniques. Consumer protection is all efforts made by the government to ensure legal certainty in providing protection to consumers. The UUPK outlines the rights and obligations of consumers and businesses. Consumer rights are divided into 9 points regarding security, comfort, consumer safety is an urgent matter in consumer protection. In sharia economic law, the stages that constitute legal protection can be given. In the study of Islamic fiqh related to the truth and accuracy of information When business actors promote their sales occupy at the study stage. In recent years Indonesia has experienced several phenomena that occur in the community, but these phenomena are negative because they make it difficult for people to carry out their activities such as hoarding masks, and hoarding cooking oil. The relationship between sociology of anthropology and Islamic economic law on consumer protection is that, phenomena that occur in society, can have an impact not on legal, religious, or social aspects. Referring to the issue of consumer protection on social media, there are three points that are the focus of the problem, namely the Revision of the Consumer Protection Law. Consumer protection of non-conforming goods (defective, different orders, fraud). Consumer protection of Financial Technology